Nilai Ekonomi dan Manfaat Pemeliharaan Sapi Madura Upaya Meningkatkan Penghasilan Petani - Hopid, Hopid; Rahman, Sindi Arista (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Raising Madurese cattle has a significant economic impact, affecting the sustainability of the local economy and the welfare of farmers as well as bringing non-negligible benefits to social and environmental welfare. This study aims to analyse the economic value and benefits of raising Madurese cattle. The urgency of this research is the economic contribution, uniqueness, and potential of its research on the economic value and benefits of raising Madura cattle is very important and urgent. The results of this study show that Madura cattle rearing provides positive economic value and has the potential to be a stable source of additional income for farmers with a net profit of Rp 6,961,000 during the rearing period. Meanwhile, the value of benefits obtained from cattle rearing include increasing family assets or savings, being a financial guarantee during emergencies, as agricultural labour (ploughing tegal) and producing organic fertiliser to improve soil fertility. Strategies that need to be carried out for cattle development to increase farmers' income are four elements, namely improving the quality of superior cattle breeds through the application of artificial insemination technology, increasing access to capital for farmers, increasing training and animal husbandry technology, and quality animal feed fermentation technology.